Universal PCR assays to detect Candida FKS and ERG11 mutations - Dr Yuk Yam Cheung; Mr. Zhi Hao ZHANG; Ms. Wing Yan CHAR; Mr. Tsun Hang FONG; Mr. Chun Yu LI (International Journal of Infectious Diseases)
Introduction: The emergence of antifungal resistance in Candida species presents significant challenges in managing infections, particularly among immunocompromised patients. This study aimed to develop rapid molecular assays for detecting mutations in the FKS genes across four clinically significant Candida species: Candida albicans, C. glabrata, C. tropicalis, and C. parapsilosis, as well as mutations in the ERG11 gene in C. albicans, C. tropicalis, and C. parapsilosis. Mutations in the FKS genes are known to confer resistance to echinocandins, while ERG11 mutations are associated with resistance to azoles. Therefore, the detection of these mutations is crucial for effective patient management and treatment outcomes. Methods: To achieve this, we developed two universal polymerase chain reaction (PCR) assays: one for detecting FKS mutations and another for ERG11 mutations. Also, antifungal susceptibility testing was performed against echinocandins (micafungin and anidulafungin) and azoles (fluconazole and voriconazole) in accordance with the Clinical and Laboratory Standards Institute guidelines (M27-A3 for testing and M27M44S for interpretation).In this study, we included six American Type Culture Collection (ATCC) type strains, six blood culture isolates, and eight laboratory-derived strains exhibiting resistance to echinocandins or azoles. Results: We identified five FKS mutations and two ERG11 mutations, both of which correlated with elevated minimum inhibitory concentrations for the antifungal agents tested. These findings indicate significant relationships between specific mutations and antifungal resistance. Discussion: The two assays have a test turnaround time of approximately six hours for amplification and sequencing of the target regions, allowing mutation detection results to be readily available on the same day blood cultures become positive. Identifying these mutations enables healthcare providers to predict treatment outcomes before the antifungal susceptibility tests results are available and to assess the potential for therapeutic failure due to antifungal resistance. This information is critical for informing therapeutic strategies in clinical settings. For patients infected with Candida carrying FKS and/or ERG11 mutations, alternative treatment options may be necessary, underscoring the importance of rapid and accurate diagnostic tools for the detection of the mutations. Moreover, the developed assays can facilitate ongoing surveillance of antifungal resistance patterns in clinical isolates as the resistance landscape continues to evolve. Conclusion: In conclusion, the developed universal PCR assays for detecting FKS and ERG11 mutations in this study are potential rapid diagnostics tools for antifungal resistance. The established correlation between these mutations and elevated MICs underscores the clinical utility of these assays as valuable tools in microbiology laboratories. By enabling timely detection of the mutations, these assays have great potential to optimize antifungal therapy and improve patient outcomes.